Answer:
x = -5 * (2)^(n-1)
Explanation:
If we look a the supplied n elements of the sequence, and we divide each of them by -5.
1 = -5, -5/-5 = 1
2 = -10, -10/-5 = 2
3 = -20, -20/-5 = 4
4 = -40, -40/-5 = 8
We realize that we have all the powers of 2 there.
So the formula will start with -5 (the first element), then multiplied by a power of 2.
![x = -5 (2)^(n-1)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/dsxctgaolmgz2lde97j9xgejxll4hfbxr0.png)
We can verify for the 4th element, where n = 4:
![x = -5 (2)^(n-1) = -5 (2)^(4-1) = -5 (2)^(3) = -5 * 8 = -40](https://img.qammunity.org/2020/formulas/mathematics/middle-school/qm2sl11ed2g9hulvmba36n3cvvzb5a7ugt.png)